Assessment of the Anti-Inflammatory and Antioxidant Activities of Adansonia digitata L Combined with doxorubicin - Abeer Mansour Abdel Rasool; Alyaa Ali Al-Safo (International Journal of Medical Toxicology and Legal Medicine, 2024)
Doxorubicin is a highly effective chemotherapeutic agent; however, its application is limited by its toxic properties in the treatment of several cancers, including acute leukemia and lymphomas, among others. These toxic effects significantly constrain its clinical applications. The baobab (Adansonia digitata L.) is a multi-purpose plant with frequent uses and, importantly, considerable medicinal value. Its seeds serve many purposes, including thickening soups and acting as a flavor enhancer when cooked. The aim of this study was to establish the potential anti-inflammatory and antioxidant activities of Adansonia digitata L. combined with doxorubicin. Materials and Methods: The study involved forty rats divided into four groups to evaluate the effects of Adansonia digitata extract and doxorubicin. Biochemical examinations assessed total antioxidant status and biomarkers of inflammation, which are important in evaluating the level of oxidative stress and inflammation in the body. Immunohistochemical testing of caspase 3 in rat kidneys and livers revealed numerous pathological changes. The present study aimed to assess the anti-inflammatory and antioxidant activities of Adansonia digitata L. when used in combination with doxorubicin.